Enhancing Early Mathematics Learning Through an Interactive Storybook: A Development and Validation Study - Solfiah, Yeni; Nazri, Mohd; Risma, Devi; Satria, Defni; Pratiwi, Nanda; Eriani, Eva; Mastuinda, Mastuinda (FKIP Universitas Lampung, 2025)
Enhancing Early Mathematics Learning Through an Interactive Storybook: A Development and Validation Study. Objective: This research aims to develop and implement an active mathematics learning paradigm for early childhood through illustrated storybooks that integrate fundamental mathematical concepts, namely numbers, patterns, geometry, measurement, and statistics. The goal is to provide a developmentally appropriate platform that encourages engagement, improves math proficiency, hones problem-solving skills, and makes learning more meaningful and enjoyable. Methods: The methodology used is a development research based on the Dick and Carey model. The validation process involved mathematicians, early childhood education experts, kindergarten educators, and media experts. Data were obtained through surveys, interviews, observations, and limited trials involving 14 children aged 5–6 years in Pekanbaru, Riau Province, Indonesia. Quantitative data analysis employed descriptive statistics, pretest-posttest comparisons, normality tests, and homogeneity tests. At the same time, qualitative data were obtained from expert evaluations and instructor comments. Findings: The validation results showed that the developed media met the criteria of validity, practicality, and efficacy, with scores from PAUD experts of 88.00%, mathematics experts of 89.33%, early childhood teachers of 81.54%, and media experts of 88.00%, with an overall category of